Unidad Didáctica. Aprendizaje Del Algebra Mediante El Algebra Geométrica Para Estudiantes Del Ciclo IV De La Educación Para Jóvenes Y Adultos Del IED Alimrante Padilla (2018)
The aim of this paper is to propose a didactic unit to make the learning of algebra more comprehensible, which corresponds to one of the tools of variational thinking, for the students of cycle IV of education for young people and adults of the IED Almirante Padilla de the weekend day